(untitled) (Teresa Vigetti: Revista de Trabajo Social, 2025)
In what follows, I address several aspects that have been and continue to be the subject of debate, problematization, and reflection within the professional collective. I start with expressions such as ’oral tradition and the interventive nature of our field,’ treating them as myths to advance in a process of deconstruction by appealing to critique and historical revision. I discuss both expressions, accounting for the interests at play within them, using historical events as witnesses. In this sense, I invite us to think about social work through the edges of hegemonic protocols to recognize the tensions that intersect us when approaching it epistemologically. I conclude with reflections on writing in social work from a perspective that transcends the question of norms and written genres.